An Alphabet from the Days of the Judges - Demsky, Aaron (The Biblical archaeology review, 1978)
At a site called Izbet Sartah, now believed by some scholars, to be Biblical Ebenezer, a recent excavation by Tel Aviv and Bar-Ilan Universities has uncovered a small clay potsherd—unrelated to the Biblical story—which, however, is the most important single find of the excavation. The sherd contains the longest proto-Canaanite inscription ever discovered.a The […]